2009
DOI: 10.1080/00918360903187812
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sibling Relationships of Sexual Minority Youth

Abstract: The purpose of this study was to examine the relationships of sexual minority youth and their siblings. The participants were 56 lesbian, gay, bisexual, or transgender individuals ranging in age from 18 to 24 years, who reported information about a total of 107 siblings. Respondents completed a demographic data questionnaire as well as adapted versions of the Sibling Closeness Scale (SCS) and the Sibling Approval of Sexual Behavior Scale (SASBS) to describe their relationship with each of their siblings. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
6
37
0
1
Order By: Relevance
“…Similarly, another study found that 63% of gay men and lesbians sampled had come out to their siblings, and 60% of those who had done so rated their siblings as supportive and accepting of their sexual orientation (Beals & Peplau, ). In a study that examined 56 LGBT youths' perceptions of their sibling relationships, Toomey and Richardson () found that participants were most likely to disclose to their mothers and second most likely to disclose to a sibling. Yet another study found that few LGBQ youth reported negative reactions from siblings following disclosure, but when negative reactions did occur, they were more likely to come from male than female siblings (D'Augelli, Grossman, & Stark, ).…”
Section: Disclosurementioning
confidence: 99%
“…Similarly, another study found that 63% of gay men and lesbians sampled had come out to their siblings, and 60% of those who had done so rated their siblings as supportive and accepting of their sexual orientation (Beals & Peplau, ). In a study that examined 56 LGBT youths' perceptions of their sibling relationships, Toomey and Richardson () found that participants were most likely to disclose to their mothers and second most likely to disclose to a sibling. Yet another study found that few LGBQ youth reported negative reactions from siblings following disclosure, but when negative reactions did occur, they were more likely to come from male than female siblings (D'Augelli, Grossman, & Stark, ).…”
Section: Disclosurementioning
confidence: 99%
“…With regards to siblings, a range of studies, including Gorman‐Murray () and Toomey and Richardson (), suggested that young lesbian and gay people often come out to their siblings before coming out to their parents, generally to test the waters and to assess the potential consequences. Sometimes, they also seek their sibling's support in coming out to their parents (Beatty, ; Savin‐Williams, ).…”
Section: Mom Dad and Siblingsmentioning
confidence: 99%
“…Sometimes, they also seek their sibling's support in coming out to their parents (Beatty, ; Savin‐Williams, ). Although research that compares siblings' reactions to parents' reactions is scant, the first disclosure within a family is often to a sibling (Toomey & Richardson, ). Although siblings are generally supportive (Gorman‐Murray, ), a few studies (Kadushin, ; Toomey & Richardson, ) found that sisters were more likely to support and affirm their lesbian/gay siblings than brothers would generally do.…”
Section: Mom Dad and Siblingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le point de vue des pères comme celui des parents issus de communautés ethnoculturelles sont peu représentés dans le cadre des recherches, limitant considérablement la pluralité et la diversité des expériences parentales. Également, peu d'études ont documenté le point de vue des membres de la fratrie, c'est-à-dire des frères et soeurs de la personne qui s'identifie comme gai ou lesbienne (Toomey et Richardson, 2009). Pourtant, la fratrie a une influence évidente sur les interactions familiales (D'Augelli et al, 2010 ;Heatherington et Lavner, 2008 ;Hilton et Szymanski, 2011).…”
Section: Limites Des Recherches Et Prospectivesunclassified